2020
DOI: 10.5539/ijel.v10n5p221
|View full text |Cite
|
Sign up to set email alerts
|

‘I Couldn’t Join the Session’: Benefits and Challenges of Blended Learning amid COVID-19 from EFL Students

Abstract: COVID-19 has changed the process of teaching considerably, as educational institutions around the world moved to adopt blended learning initiatives to ensure continuity, while managing the spread of this infectious disease. All Saudi Arabia’s universities have continued to deliver courses via digital platforms. This study draws on traditional views about blended learning (Sharma, 2010) and examines the pedagogical changes to English courses implemented at King Saud University following the start of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 14 publications
8
63
1
3
Order By: Relevance
“…And they would look forward to using Blackboard for their learning next year (M = 3.81), believing that their instructors are good enough to provide active, interactive learning activities via Blackboard (M = 3.81), which makes them really enjoy learning online via Blackboard (M = 3.66). This result concurs with a plethora of studies recently conducted during the time this study was in progress or a little before (e.g., Alowedi, 2020;Althobaiti, 2020;Alsulami, 2016;Al-Washahy & Amaar, 2015;Cavanaugh & Song, 2014;Dahmash, 2020;Han & Ellis, 2019;Gulbinskienė et al, 2017).…”
Section: Students' Attitudes Survey Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…And they would look forward to using Blackboard for their learning next year (M = 3.81), believing that their instructors are good enough to provide active, interactive learning activities via Blackboard (M = 3.81), which makes them really enjoy learning online via Blackboard (M = 3.66). This result concurs with a plethora of studies recently conducted during the time this study was in progress or a little before (e.g., Alowedi, 2020;Althobaiti, 2020;Alsulami, 2016;Al-Washahy & Amaar, 2015;Cavanaugh & Song, 2014;Dahmash, 2020;Han & Ellis, 2019;Gulbinskienė et al, 2017).…”
Section: Students' Attitudes Survey Resultssupporting
confidence: 91%
“…Additionally, other studies show that VLEs with online video and audio tools (e.g., YouTube, Skype), also available via smartphone and tablet applications, have all a positive effect on learning English (Alsulami, 2016;Shafiee, Akbari, & Hajijalili, 2019). These studies and others (Al Bataineh, Banikalef, & Albashtawi, 2019;Dahmash, 2020) found that the nature of individualized 'student-to-computer' interaction promotes self-directed learning and improve attitudes towards learning English in virtual or blended learning environments.…”
Section: Virtual Education In Foreign Language Education: Perceptions and Attitudesmentioning
confidence: 89%
See 1 more Smart Citation
“…English language related studies during the Covid-19 process (between March 2020 and February 2021) (Aji et al, 2020;Allo, 2020;Almekhlafy, 2020;Andriivna et al, 2020;Ariyanti, 2020;Astuti & Solikhah, 2021;Atmojo & Nugroho, 2020;Bailey & Lee, 2020;Chiatoh & Chia, 2020;Dahmash, 2020;Davies et al, 2020;Destianingsih & Satria, 2020;Farrah & Al-Bakry, 2020;Fatima, 2020;Fitria, 2020;Forrester, 2020;Fuad et al, 2020;Fuentes Hernández et al, 2020;Gao & Zhang, 2020;Hadianti & Arisandi, 2020;Hafidz, 2020;Hakim, 2020;Hamid, 2020;Hartshorn & Mcmurry, 2020;Hazaea et al, 2021;Hodges et al, 2020b;Hopp & Thoma, 2020;Huang et al, 2021;Kamhi-Stein et al, 2020;Karakuzu et al, 2020;Karataş & Tuncer, 2020;Karim & Hasan, 2020;Kawinkoonlasate, 2020;Khafaga, 2021;Kholis, 2020;Krishan et al, 2020;Kusumawati, 2020;Li et al, 2020;Lie et al, 2020;Loo, 2020;…”
Section: Study Focus Authors Nmentioning
confidence: 99%
“…The study results revealed that most EFL learners are not satisfied with continuing online learning, because they are not achieving the anticipated improvement in language learning performance. Dahmash (2020) explored the benefits and challenges of blended learning during the spread of COVID-19 from the perspective of English as a foreign language (EFL) student at King Saud University. The results show that blended learning profited the EFL students by endorsing their writing skills and persuading them to search online, alongside fitting their circumstances and being economical.…”
Section: Challengesmentioning
confidence: 99%